Pengaruh Kompensasi dan Motivasi Kerja Terhadap Kinerja Karyawan: Survei pada Karyawan Restoran dan Pemancingan Mang Ajo Karawang - Ade Dwi Priptiyani; Netti Nurlenawati; Flora Patricia Anggela (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to determine the effect of compensation and work motivation on employee performance at Mang Ajo Fishing and Restaurant. The research method used in this research is quantitative with descriptive and verification. The sampling technique in this study was 60 people. There is a low relationship between compensation and work motivation from a correlation analysis of 0.227. The t test shows that the t value for compensation is 7.468 and the t value for work motivation is 0.538, all of which show greater t table is 2.002. The F test obtained Fhitung 30.57> Ftabel 3.15 or the significance level (sig) 0.000 <0.05 so that the hypothesis that compensation and work motivation together have an effect on employee performance at Mang Ajo Restaurant and Fishing.